2014
DOI: 10.1155/2014/160695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Combination of Gelam Honey and Ginger on Oxidative Stress and Metabolic Profile in Streptozotocin-Induced Diabetic Sprague-Dawley Rats

Abstract: Diabetic complications occur as a result of increased reactive oxygen species (ROS) due to long term hyperglycaemia. Honey and ginger have been shown to exhibit antioxidant activity which can scavenge ROS. The main aim of this study was to evaluate the antioxidant and antidiabetic effects of gelam honey, ginger, and their combination. Sprague-Dawley rats were divided into 2 major groups which consisted of diabetic and nondiabetic rats. Diabetes was induced with streptozotocin intramuscularly (55 mg/kg body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…Of these two types, the latter is the more prevalent form and generally receives more attention. To date, a number of studies have demonstrated that ginger extract can exert beneficial effects on serum glucose and tissue glycogen content in alloxan-induced 39 and streptozotocin-induced diabetic animal models [40][41][42][44][45][46][47] through enhancing the peripheral utilization of glucose, regulating the activities of glycolytic enzymes, and limiting gluconeogenic formation. 45 Ginger extract could increase the activities of glycolytic enzymes, which drives the metabolic degradation of glucose to form pyruvate.…”
Section: Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these two types, the latter is the more prevalent form and generally receives more attention. To date, a number of studies have demonstrated that ginger extract can exert beneficial effects on serum glucose and tissue glycogen content in alloxan-induced 39 and streptozotocin-induced diabetic animal models [40][41][42][44][45][46][47] through enhancing the peripheral utilization of glucose, regulating the activities of glycolytic enzymes, and limiting gluconeogenic formation. 45 Ginger extract could increase the activities of glycolytic enzymes, which drives the metabolic degradation of glucose to form pyruvate.…”
Section: Diabetesmentioning
confidence: 99%
“…Recent studies indicated that ginger and its bioactive components exerted a therapeutic protective effect in diabetes by regulating oxidative stress markers and decreasing activities of antioxidant enzymes. 25,43,44,46,47 Furthermore, it was demonstrated that 6-gingerol could protect pancreatic ␤ cells from oxidative stress by reducing the artificial d-glyceraldehyde-induced increase in the intracellular reactive oxygen species (ROS) level in RIN-5F cells. 48 On the other hand, it is generally accepted that inflammation is usually associated with the pathogenesis of T2DM.…”
Section: Diabetesmentioning
confidence: 99%
“…However, Bahrami and his colleagues reported that honey had no significant difference in blood glucose concentration of diabetic patients with type 2 diabetes. When honey used to treat diabetic rats, they showed no improvement in blood glucose concentration [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Kombinasi madu dan rempah-rempah seperti temulawak dan jahe diduga dapat menaikkan aktivitas antioksidannya. Kombinasi madu gelam dan jahe dapat menurunkan kadar malonaldehid sebagai hasil oksidasi lipid pada tikus diabetes (Sani et al, 2014). Hasil penelitian Septiana et al (2017) menunjukkan bahwa minuman temulawak mempunyai aktivitas antioksidan lebih besar dibandingkan minuman kunyit, jahe maupun minuman beras kencur.…”
Section: Pendahuluanunclassified